Types of Ovitrap Colors Preferred by Aedes aegypti Mosquitoes for Egg Laying in Mokoau Community Health Center Area: Types of Ovitrap Colors Preferred by Aedes aegypti Mosquitoes for Egg Laying in Mokoau Community Health Center Area - Fajirin Alam Syah; Lili Herliana; Habriani (Pena Medika : Jurnal Kesehatan, 2025)
Dengue Hemorrhagic Fever (DHF) is a dangerous infectious disease that can cause death in a short period. Despite efforts to eradicate mosquitoes, vector control, such as the use of Ovitraps, which are effective in reducing the Aedes aegypti mosquito population, has become a primary focus. This study aims to assess the effectiveness of Ovitrap colors most preferred by Aedes aegypti mosquitoes for laying eggs in the working area of the Mokoau Health Center. This research used a pre-experimental method with an observational design to evaluate the preference of Aedes aegypti mosquitoes in laying their eggs in Ovitraps of various colors, using tap water (PDAM water) as the medium. The study was conducted in the working area of the Mokoau Health Center from July to August 2024. The population and sample of the study consisted of female Aedes aegypti mosquitoes that laid eggs in Ovitraps painted red, orange, yellow, green, blue, and black, with 10 Ovitraps of each color. Data were collected by installing Ovitraps in the study area. Data analysis was conducted descriptively to present the observations, complemented by a normality test to determine whether the data distribution was normal or not. The results of this study indicate that Aedes aegypti mosquitoes have several color preferences for laying eggs, including black, red, blue, green, and orange. Based on the analysis conducted, the mosquitoes laid the most eggs in yellow-colored Ovitraps, with an average of 33.8 eggs (27.37%). This was followed by black Ovitraps with an average of 25.10 eggs (20.32%), red Ovitraps with an average of 19.00 eggs (15.38%), blue Ovitraps with an average of 16.70 eggs (13.52%), green Ovitraps with an average of 15.40 eggs (12.47%), and orange Ovitraps with an average of 13.50 eggs (10.93%). These findings highlight that the choice of Ovitrap color can influence the effectiveness of mosquito egg capture, with yellow offering greater attraction and being a more effective option in controlling the Aedes aegypti population. Keywords: Ovitrap, Aedes aegypti, Mokoau Health Center